2017
DOI: 10.3390/su9010132
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ammonia Volatilization Losses and Nitrogen Utilization during the Rice Growing Season in Alkaline Salt-Affected Soils

Abstract: Abstract:The objectives of this study were to evaluate the effects of different fertilizer types and application rates on ammonia volatilization loss and to explore nitrogen distribution and nitrogen use efficiency using the 15 N isotope tracing technique in different alkaline salt-affected conditions in the Songnen Plain, Northeast China. The results showed a decreasing trend in ammonia volatilization loss from ammonium nitrate and ammonium sulfate, but not that from urea, as the electrical conductivity gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 34 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…However, the degree will also depend on the specific fertilizer and its effect on soil pH. In a study involving ammonia volatilization from an alkaline salt-affected soil cultivated with rice, Li et al [56] found that ammonia volatilization increased rapidly with pH and peaked at pH 8.6. Ammonia volatilization is strongly correlated with pH and calcium carbonate, which suggested that the soil pH was a key factor in ammonia volatilization because calcium carbonate increases soil pH which in turn controls the concentration of ammonia and ammonium in soil solution [57].…”
Section: Ammonia Volatilizationmentioning
confidence: 99%
“…However, the degree will also depend on the specific fertilizer and its effect on soil pH. In a study involving ammonia volatilization from an alkaline salt-affected soil cultivated with rice, Li et al [56] found that ammonia volatilization increased rapidly with pH and peaked at pH 8.6. Ammonia volatilization is strongly correlated with pH and calcium carbonate, which suggested that the soil pH was a key factor in ammonia volatilization because calcium carbonate increases soil pH which in turn controls the concentration of ammonia and ammonium in soil solution [57].…”
Section: Ammonia Volatilizationmentioning
confidence: 99%
“…Although there was a large database with estimates of NH 3 volatilization based on the types of N fertilizers and their uses, most of these studies were conducted under temperate and subtropical conditions [9,39,40]. Because NH 3 emissions after fertilizer application vary with soil type, pH, and temperature, inventories should assign emission factors for different fertilizers in different countries according to the prevailing soil and climate category in order to obtain reliable estimates of nitrogen fertilizer impact analysis for different crops.…”
Section: Ammonia Volatilizationmentioning
confidence: 99%
“…The low soil pH with T2 is associated with the acidity of the NPK fertilizer. Soil EC has also been implicated in ammonia emission [43]. In comparison with T2, the lower NH 4 concentrations in T3 and T4 were ascribed to the intense NH 3 volatilization during the soil incubation study.…”
Section: Discussionmentioning
confidence: 97%